Rancang Bangun Aplikasi Marketplace Tour dan Travel Di Kota Semarang - Rizal, Muhammad Syahrul; Julianto, Veri (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
Travel is one way to let go of fatigue and fatigue after doing activities every day. Most people to search for travel packages according to available financial conditions are still difficult to do, because they have to find contacts and ask about every travel tour they know. This markerplace application was made with the aim of helping the community to search for travel packages from various available travel tours, making it easier for people to find travel packages according to their conditions and desires. This application is created using the PHP programming language and MySQL as the database. The stages of making this application use the sprint and scrum design methods. Based on the tests carried out to users, this application in functionality runs as expected and gets a good response from users.